Are frailty components associated with disability in specific activities of daily living in community-dwelling older adults? A multicenter Canadian study. (November 2017) - Provencher, Véronique; Béland, François; Demers, Louise; Desrosiers, Johanne; Bier, Nathalie; Ávila-Funes, José Alberto; Galand, Claude; Julien, Dominic; Fletcher, John D.; Trottier, Lise; Hami, Benyahia
Highlights: Our study documented how individual components of frailty and disability in specific activities of daily living (ADL) were related. Low physical activity and slowness were revealed to be important contributing frailty components to disability in most ADL. These mobility-related frailty components are relevant targets for disability prevention and rehabilitation programs. Most frailty components were significantly linked to disability in transportation, shopping, housekeeping, food preparation and purchasing . Appropriate interventions should support participation in these ADL (e.g., food preparation) strongly associated with the frailty phenotype. Abstract: Current studies show the relevance of geriatric prevention and rehabilitation programs to slow down the development of disability in community-dwelling older adults who are becoming frail. This evidence reveals the importance of improving knowledge on how individual components of frailty and specific disability in basic and instrumental activities of daily living (ADL) are related, to offer early, targeted, and tailored interventions. The objective was to examine the association between each of the five frailty phenotype components ( weakness, slowness, exhaustion, low physical activity, weight loss ) and disability in specific ADL pertaining to physical aspects ( bathing, dressing, cutting toe nails, transportation, shopping, housekeeping, food purchasing, food preparation ) and cognitive aspects ( finances, telephone, medication ). A cross-sectional design involving 1643 community-dwelling older adults (65+) from the longitudinal multi-center FRéLE study was used. Disability was defined as needing help or being unable to perform specific ADL. Multiple logistic regressions were adjusted for socio-demographic characteristics, clinical variables, and for 4 other frailty components. Results showed that low physical activity and slowness were significantly linked to disability in all physical and cognitive aspects of ADL (OR: 1.71–9.42; p < 0.05), except using the telephone . Notably, all frailty components except weight loss were associated with disability in the physical aspects of instrumental ADL ( transportation, shopping, housekeeping, food purchasing, food preparation ) (OR: 1.73–9.42; p < 0.05). This study helped identify the relevant frailty components as targets in community-based prevention and rehabilitation programs. Easily imbedded interventions in daily routines should be promoted earlier in the frailty process to delay or reduce disability.